1999
DOI: 10.1021/es980631h
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Gastrointestinal Method To Estimate Bioavailable Arsenic in Contaminated Soils and Solid Media

Abstract: A method was developed to simulate the human gastrointestinal environment and to estimate bioavailability of arsenic in contaminated soil and solid media. In this in vitro gastrointestinal (IVG) method, arsenic is sequentially extracted from contaminated soil with simulated gastric and intestinal solutions. A modified IVG-AB method, where iron hydroxide gel is used to simulate the absorption of arsenic, was also evaluated. Fifteen contaminated soils collected from mining/smelter sites ranging from 401 to 17 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
371
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 438 publications
(383 citation statements)
references
References 25 publications
7
371
0
5
Order By: Relevance
“…2). In agreement with other researchers (Ruby et al, 1996;Rodriguez et al, 1999;Ellickson et al, 2001), only slight differences were observed in the bioaccessibility of As between the gastric and intestinal phases for each soil (As bioaccessibility between gastric and instestinal phases significantly different (P < 0.05) for 18 out of 35 pairs). Yang et al (2002) found that DCB-extractable Fe oxide was the most important soil property controlling the initial degree of adsorption of As added to soil.…”
Section: The Effect Of Ageing On As Bioaccessibility In Soilssupporting
confidence: 92%
See 2 more Smart Citations
“…2). In agreement with other researchers (Ruby et al, 1996;Rodriguez et al, 1999;Ellickson et al, 2001), only slight differences were observed in the bioaccessibility of As between the gastric and intestinal phases for each soil (As bioaccessibility between gastric and instestinal phases significantly different (P < 0.05) for 18 out of 35 pairs). Yang et al (2002) found that DCB-extractable Fe oxide was the most important soil property controlling the initial degree of adsorption of As added to soil.…”
Section: The Effect Of Ageing On As Bioaccessibility In Soilssupporting
confidence: 92%
“…The physiologically based extraction test proposed by Ruby et al (1996) was employed with some modifications derived basically from the in vitro model proposed by Rodriguez et al (1999). Full details of the in vitro test procedure are described in Tang et al (2006); only brief details are given here.…”
Section: Procedures For the Physiologically Based In Vitro Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the time, cost and ethical considerations associated with in vivo methods, in vitro methods are widely used in assessing human health risk. For As contaminated soils, a strong linear relationship between As relative bioavailability (RBA) and As bioaccessibility has been reported Juhasz et al, 2009Juhasz et al, , 2014Rodriguez and Basta, 1999;Ruby et al, 1996). By establishing good in vivo-in vitro correlations, these in vitro bioaccessibility methods have been proposed as surrogates to predict the RBA for refining the risk to human health of inadvertent oral soil ingestion as an important exposure route.…”
Section: Introductionmentioning
confidence: 99%
“…By establishing good in vivo-in vitro correlations, these in vitro bioaccessibility methods have been proposed as surrogates to predict the RBA for refining the risk to human health of inadvertent oral soil ingestion as an important exposure route. To date, numerous in vitro methods have been used to assess As bioaccessibility in soils (Kelly et al, 2002;Rodriguez and Basta, 1999;Ruby et al, 1996;Wragg et al, 2011). A respectable amount of information is available regarding the comparison of in vitro methods for the assessment of As bioaccessibility.…”
Section: Introductionmentioning
confidence: 99%